Detection of Antibiotic Resistance Salmonella Sp Isolated from Layer Chicken Farm in Sesaot West Lombok - April, Berlian Ronaldi; Agustin, Alfiana Laili Dwi; Atma, Candra Dwi; Tirtasari, Kunti (Media Kedokteran Hewan, 2022)
Antibiotic resistance is a global problem related to human and animal health. Antibiotic resistance occurs when bacteria acquire a resistant gene that allows them to survive when exposed to the antibiotic. Production animals and their production environment are considered as a reservoir for the emergence of resistant bacteria that transfer to humans either directly or indirectly. Narmada Subdistrict in West Lombok is one of the districts that have a large population of poultry. One of the infectious diseases that often attacks poultry and is treated using antibiotics is Salmonella sp. This study aims to determine the data on antibiotic resistance in Salmonella sp. This resistance data can be used as an effort to prevent antibiotic resistance against Sallmonella sp bacteria in layer chicken farms in Sesaot, West Lombok. This research using eight Salmonella sp. isolates, they were tested with antibiotics PenicillinG, Tetracycline and Oxytetracycline. Bacterial resistance test was carried out after the results obtained from the identification of bacteria, Salmonella sp. The results obtained from eight Salmonella sp isolates tested for antibiotic resistance, antibiotics were categorized as susceptible to Penicillin G (75%), Oxytetracycline (12.5%), and Tetracycline (12.5%). Antibiotics were categorized as intermediates consisting of Penicillin G (0.0%), Oxytetracyline (12.5%), and Tetracycline (50%). and Antibiotics categorized as resistant consisted of Penicillin G (25%), Oxytetracycline (75%), and Tetracycline (37.5%).